1994
DOI: 10.1159/000227391
|View full text |Cite
|
Sign up to set email alerts
|

CA15.3, CEA and TPA Tumor Markers in the Early Diagnosis of Breast Cancer Relapse

Abstract: To evaluate the utility of CA 15.3 in detecting breast cancer relapse before clinical evidence of metastatic disease, serial determinations of CA 15.3 serum levels were made in 444 disease-free patients after surgery, during 36 months of follow-up. The results were compared with carcinoembryonic antigen (CEA) and tissue polypeptide antigen (TPA). The study found CA 15.3 to be more sensitive as an early indicator of relapse than CEA or TPA; moreover, simultaneous determination of the other markers offers no inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 8 publications
0
11
0
1
Order By: Relevance
“…The use of CA15.3 for early detection of metastases seems to be promising (12) and their use for measuring therapeutic response in metastatic disease is widely accepted (13).Women with resected breast carcinoma who received G-CSF (Granulocyte Colony Stimulating Factor) primed chemotherapy showed serum CA 15-3 elevation due to an increase in peripheral blood neutrophil number and induced neutrophil cytoplasmic MUC1 expression which was caused by G-CSF (14). The study by Safi et al (15) showed that CA15.3 was significantly better than CEA in the detection of breast cancer metastases.…”
Section: Resultsmentioning
confidence: 99%
“…The use of CA15.3 for early detection of metastases seems to be promising (12) and their use for measuring therapeutic response in metastatic disease is widely accepted (13).Women with resected breast carcinoma who received G-CSF (Granulocyte Colony Stimulating Factor) primed chemotherapy showed serum CA 15-3 elevation due to an increase in peripheral blood neutrophil number and induced neutrophil cytoplasmic MUC1 expression which was caused by G-CSF (14). The study by Safi et al (15) showed that CA15.3 was significantly better than CEA in the detection of breast cancer metastases.…”
Section: Resultsmentioning
confidence: 99%
“…It is generally agreed that tumour markers in breast cancer patients are not a tool for primary diagnosis, because of their low sensitivity and specificity (Tondini et al, 1989;Fateh-Moghadam and Stieber, 1993;Lamerz et al, 1993). Their use for early detection of metastases seems to be promising (Lamerz et al, 1991;Stieber et al, 1992;Vizcarra et al, 1994;O'Hanlon et al, 1995) and their use for measuring therapeutic response in metastatic disease is widely accepted (Tondini et al, 1988;Dnistrian et al, 1991;Robertson et al, 1991;Safi et al, 1991). Many studies tried to assess the prognostic role of these tumour markers (some analysed in serum, some in tissue), but most of them had low patient numbers or short follow-up periods, and used only univariate analyses (Myers Tormey and Waalkes, 1978;Bezwoda et al, 1981;Mansour et al, 1983;Kallioniemi et al, 1988;Hammer et al, 1992;O'Hanlon et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…These antibodies have been used for immunohistochemical detection of episialin as a marker of epithelial differentiation in histologic preparations 28 and for enzyme immunoassay quantitation of episialin as a tumor marker in serum. [29][30][31] Variable levels of MUC1 expression also have been demonstrated at the RNA level in many human epithelial tissues by using Northern blot analysis, RT-PCR, or both. 19 Consistently high levels of MUC1 expression have been demonstrated in breast cancer cells, 19 and it has been suggested that RT-PCR detection of MUC1 transcripts may be useful for the identification of micrometastases from breast cancer.…”
mentioning
confidence: 99%